2016
DOI: 10.1101/055848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kin Recognition in a Clonal Fish,Poecilia Formosa

Abstract: Relatedness strongly influences social behaviors in a wide variety of species. For most species, the highest typical degree of relatedness is between full siblings with 50% shared genes. However, this is poorly understood in species with unusually high relatedness between individuals: clonal organisms. Although there has been some investigation into clonal invertebrates and yeast, nothing is known about kin selection in clonal vertebrates. We show that a clonal fish, the Amazon molly (Poecilia formosa), can di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Indeed, there was no difference between unimodal (visual or chemical only) or bimodal (the combination of visual and chemical) cues. This was confirmed in a field based experiment, where in highly turbid environments, Amazon mollies depended on chemical cues more readily than in the laboratory, 1 where visual cues were more predominant (Makowicz et al 2016). Makowicz et al (2016) predicted that one of the adaptive values of this behavior was to regulate the aggressive behaviors found in this species.…”
Section: Clonal Recognition In Amazonsmentioning
confidence: 68%
See 1 more Smart Citation
“…Indeed, there was no difference between unimodal (visual or chemical only) or bimodal (the combination of visual and chemical) cues. This was confirmed in a field based experiment, where in highly turbid environments, Amazon mollies depended on chemical cues more readily than in the laboratory, 1 where visual cues were more predominant (Makowicz et al 2016). Makowicz et al (2016) predicted that one of the adaptive values of this behavior was to regulate the aggressive behaviors found in this species.…”
Section: Clonal Recognition In Amazonsmentioning
confidence: 68%
“…Recent work has shown that Amazon mollies are able to recognize and prefer clonal sisters to non-sisters (Makowicz et al 2016). The existence of kin recognition in this species is interesting in and of itself, however, the study also showed that Amazon females could discriminate between clonal types using visual only and chemical only cues.…”
Section: Clonal Recognition In Amazonsmentioning
confidence: 83%
“…Chemical information alone appears ineffective, although it is otherwise used widely in swordtails and other Poeciliids (Fisher & Rosenthal, ; McLennan & Ryan, ; Wong et al., ). We do not think that the method used here led to the lack of response, because in a different study using similar containers and investigating clonal recognition in the Amazon molly, females were able to recognize kin using all modalities investigated here (Makowicz et al., ). This strong role of visual communication is not a completely unexpected result, as visual displays are known to be important in swordtails, both in male contests and for acquiring mates.…”
Section: Discussionmentioning
confidence: 90%
“…Data were then normalized using √arc (sin) transformation. Any trials in which the female showed a side bias (more than 85% of time on one side; McCoy et al., ; Makowicz et al., ) were excluded from analysis. Eighteen trials were excluded due to side bias, but a binomial test indicated that side biases were distributed randomly between the two sides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation